FAKTOR - FAKTOR YANG MEMPENGARUHI TERJADINYA KETUBAN PECAH DINI PADA KEHAMILAN ATERM DI RUMAH SAKIT AURA SYIFA KEDIRI - nugrahani, Rosi rizqi (Universitas Nusantara PGRI Kediri, 2019)
Premature rupture of membranes is the rupture of the membranes for one hour before there are signs labour. Benefit of research to determine the risk factors for premature rupture of membranes at term pregnancy is to anticipate the incidence of premature rupture of membranes. The purpose of this study was to determine the risk factors for premature rupture of membranes at term pregnancy. This study uses a prospective cohort design analytic population of 147 people with purposive sampling technique sampling obtained 60 samples. This study was conducted on 18 April to 18 May 2013. This research instruments such as questionnaires. The analysis using relative risk test results opportunities ≤ 20 years of age and> 35 years experience 4 times the risk of premature rupture of membranes than the age of 21 years old - 35 years old, working mother factor 0.8 times the risk of experiencing premature rupture than the mother does not work, parity factor of > 3 times the risk of having two premature rupture than 1-3 parity, history of premature rupture factor 0.6 times the risk of experiencing premature rupture history than that no premature rupture of membranes, twin pregnancy factor has the same risk of experiencing premature rupture . From the analysis it can be seen that the risk factors of age, occupation, parity, and history of premature rupture of membranes are at increased risk of experiencing premature rupture of membranes and pregnancy risk factors twins have the same risk of experiencing premature rupture of membranes. Recommendations from this study is considering the influence of risk factors with the incidence of premature rupture of membranes, then the health professionals to constantly strive to increase the quality of health care in midwifery care, especially antenatal care to detect risk factors that may favour the occurrence of premature rupture of membranes so as to minimize complication which may occur in the mother the baby.